The Effect of Dry-Land Quickness Training on Swimming Performance of 14-16 Ages Students - GUL, Mine; AYDOGAN, Semihcan (Asian Journal of Education and Training, 2021)
This study aimed to research the effect of dry-land quickness training for 14-16 years old male swimmers on 50 m freestyle swimming performance. 30 volunteer male athletes and 10 volunteer males in the same age group who do not sport participated in this study. Athletes were grouped who took swimming training as experiment1 (E1), experiment2 (E2) who took swimming & quickness training and control (C) group who did not take an exercise. Zig-zag (ZZ), Square test (ST), Illinois test (IT), and T-test were applied for quickness skills; 50 m freestyle swimming degree was computed for the swimming performance before and after the training. Findings were discussed by applying paired sample T-test for in-group, independent samples T-test and One-Way ANOVA tests were applied for intergroup comparison. There are significant differences in all the measurement parameters based on pared sample T-test analysis results (p<0.05). Also, with reference to intergroup analysis that compared E1, E2, and C groups, there are significant differences in all the parameters (p<0.05) while there is no difference between E2 and C group in ZZ, ST, K, and IT measurement parameters (p>0.05). On the other hand, there is a significant difference at 50 m freestyle swimming degree. Exercise that were applied on dry-land as an addition to swimming training have an effect on quickness and swimming performance. It can be considered to be available method for swimmers to plan their training at the appropriate time.